(untitled) (American Journal of Islam and Society, 2011)
Timothy Daniels’ Islamic Spectrum in Java critically examines the myriad of ways in which Javanese Muslims draw on religious and secular ideas to project desirable futures for their local societies, for the Indonesian nation, and for Indonesia’s place in the global economic, political, and cultural structures of the twenty-first century. This book identifies a broad range of desirable futures projected by Javanese Muslims, as well as a range of beliefs and practices that comprise Javanese Islam (12). While this engaging work is very likely to appeal to scholars in many fields, theoretically and methodologically it is foremost an anthropological study. Synthesizing symbolic and cognitive anthropology in order to “provide ‘thick description’ 1 of polysemous symbols . . . and to ascertain the social distribution of knowledge and formation of mental representations in various contexts (4),” Daniels draws primarily on ethnographic fieldwork conducted in the Yogyakarta area of south-central Java from 2003 to 2004. Daniels makes a complex argument, focusing on issues of globalization, localization, social change, identity formation, and the place of Islam in Javanese culture. He contends that in projecting a range of desirable futures, Javanese Muslims are able to negotiate globalization and directions of social change on their own terms by drawing from local culture and their interpretations of Islam in different ways. In particular, he examines to what extent particular ideological positions expressed by Javanese Muslims contribute to or undermine processes of equalization—“processes of weakening, undermining, and lessening hierarchical formations” (8). In supporting his argument, he addresses other related issues as well, including concepts of spiritual power, gender, sexuality, and class ...